Quality assurance in construction proceedings of the conference Quality assurance for the chief executive, organized by the Institution of Civil Engineers and held in London on 14 February 1989. (Thomas Telford, 1990)
A discussion of the benefits of applying formalized quality assurance systems to construction projects, providing the necessary expertise to enable senior executives to take the initiative with a commitment to the management of quality.